Enhancing strength and durability of recycled fine aggregate mixtures using steel fibers, silica fume, and latex polymers - Ali Mardani; Hatice Gizem Şahin; Yahya Kaya; Naz Mardani; Joseph J. Assaad; Hilal El-Hassan (Developments in the Built Environment)
Recycled fine aggregates (RFA) are often prohibited in new construction applications because of their poor physical properties. This paper assesses the feasibility of incorporating steel fibers, silica fume, and latex polymers to mitigate the drop in mechanical properties and durability of RFA-modified cementitious matrices. Testing was conducted on concrete-equivalent mortars with 80–100 MPa compressive strength and later validated on corresponding concrete mixtures. Results showed that the mechanical strengths, drying shrinkage, abrasion, and freeze/thaw resistance degraded when the natural sand was replaced by 100% RFA. The use of steel fibers or silica fume was efficient in restoring these properties within ±8% of the control mix. Meanwhile, latex polymers were more efficient in enhancing the permeability and bond properties with steel reinforcement within ±5% of the control mix. The optimum percentage of steel fibers determined from the TOPSIS method was 0.5% by volume, while the silica fume and latex optimum percentages were 6% and 2.5% of binder mass, respectively.